Method for producing paper sizing agent

JP7629633B2Active Publication Date: 2025-02-14SEIKO PMC CORPORATION
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2021090309
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-28
Publication Date
2025-02-14
Estimated Expiration
2041-05-28

AI Technical Summary

Benefits of technology

【0009】 本発明の製紙用サイズ剤の製造方法により得られる製紙用サイズ剤を使用することにより、サイズ性能の優れた紙を得ることができ、特に板紙のサイズ性能を向上させることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629633000001
    Figure 0007629633000001
  • Figure 0007629633000002
    Figure 0007629633000002
  • Figure 0007629633000003
    Figure 0007629633000003
Patent Text Reader

Abstract

To provide a manufacturing method of size agent for papermaking having more excellent size effect than conventional arts.SOLUTION: A manufacturing method of size agent for papermaking is characterized by that in the following steps (I) and / or (II), iodine and / or iodine compound used as a polymerizing component is used at the amount of 50 ppm or over as iodine atom per a monomer total amount. (I): a polymerizing step of a copolymer (A) containing a hydrophobic monomer (a1) and a hydrophilic monomer (a2) as a polymerizing component. (II): a polymerizing step of a hydrophobic monomer (b) in the presence of the copolymer (A) and / or a surfactant.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a paper-making sizing agent, and more particularly to a method for producing a paper-making sizing agent which imparts excellent sizing performance to a base paper surface by coating the base paper surface. [Background technology]

[0002] Known conventional paper sizing agents include cationic solution-type paper sizing agents, such as quaternized styrene-dimethylaminoethyl (meth)acrylate copolymers and quaternized styrene-dimethylaminopropylacrylamide copolymers, which are made by dissolving a resin consisting of hydrophobic and hydrophilic parts, and anionic solution-type paper sizing agents, such as alkali metal salts of styrene-maleic acid copolymers, alkali metal salts of styrene-(meth)acrylic acid copolymers, and alkali metal salts of α-olefin maleic acid copolymers. These solution-type paper sizing agents have high viscosity at concentrations that can be sold commercially, making it difficult to increase the concentration, which is a cost problem. In addition, the sizing agent has a disadvantage in that it foams a lot, which is likely to cause problems in operability during papermaking. Therefore, it is necessary to use a large amount of defoaming agent in combination to improve operability in actual machines, and they are not satisfactory in terms of cost and sizing performance.

[0003] Emulsion types incorporating hydrophobic particles that are an improvement over these have become common in recent years. By incorporating hydrophobic particles, it is possible to reduce the viscosity of the product, and it is possible to reduce costs or foaming properties by increasing the concentration, which was difficult with solution types. These emulsion types include cationic emulsion types and anionic emulsion types. Examples of cationic emulsion types include an internal sizing agent for papermaking obtained by emulsion polymerization of a polymerizable hydrophobic monomer, preferably styrene and 2-ethylhexyl acrylate, in the presence of an epihalohydrin quaternary product of a styrene-dimethylaminoalkyl (meth)acrylate copolymer (see, for example, Patent Document 1), and an internal sizing agent for papermaking obtained by emulsion polymerization of a styrene-based compound and a (meth)acrylic acid ester having an alkyl group with 3 to 6 carbon atoms in the presence of a quaternary product of a copolymer consisting of a styrene-based compound and a dialkylaminoalkyl (meth)acrylate. Known surface sizing agents (see, for example, Patent Document 2) include a surface sizing agent for papermaking obtained by emulsion polymerization of a polymerizable hydrophobic monomer, preferably a styrene-based compound and a (meth)acrylic acid ester, in the presence of a quaternized product of a copolymer consisting of a styrene-based compound and a dialkylaminoalkyl (meth)acrylamide (see, for example, Patent Document 3). Known anionic emulsion-type surface sizing agents for papermaking include a surface sizing agent for papermaking containing an emulsion obtained by emulsion polymerization of 10 to 500 parts by weight of a hydrophobic unsaturated monomer in an aqueous solution containing 100 parts by weight of a water-soluble copolymer containing a carboxyl group-containing unsaturated monomer and a hydrophobic unsaturated monomer (see, for example, Patent Document 4).

[0004] However, the size effect was not satisfactory. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 54-006902 [Patent Document 2] Japanese Patent Application Publication No. 11-256496 [Patent Document 3] Japanese Patent Application Publication No. 11-279983 [Patent Document 4] Japanese Patent Application Publication No. 08-246391 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a method for producing a paper sizing agent which has a better sizing effect than conventional methods. [Means for solving the problem]

[0007] As a result of intensive research aimed at solving the above problems, the present inventors have found that a sizing agent obtained by polymerization in the presence of iodine and / or an iodine compound has excellent sizing effect, and have completed the present invention.

[0008] That is, the present invention, which is a means for solving the above problems, <1> A method for producing a paper sizing agent, characterized in that the paper sizing agent is obtained by using iodine and / or an iodine compound in an amount of 50 ppm or more in terms of iodine atom relative to the total amount of monomers used as polymerization components in the following steps (I) and / or (II): (I): A step of polymerizing a copolymer (A) containing a hydrophobic monomer (a1) and a hydrophilic monomer (a2) as polymerization components. (II): A step of polymerizing a hydrophobic monomer (b) in the presence of the copolymer (A) and / or a surfactant. <2> The mass ratio of the hydrophobic monomer (a1) to the hydrophilic monomer (a2) is (50 to 85):(15 to 50). <1> A method for producing the paper sizing agent according to the present invention <3> The above-mentioned copolymer (A) and hydrophobic monomer (b) are mixed in a mass ratio of copolymer (A):hydrophobic monomer (b)=(10-100):(0-90). <1> or <2> A method for producing the paper sizing agent according to the present invention <4> The hydrophilic monomer (a2) of the copolymer (A) contains at least one selected from the group consisting of a vinyl monomer containing a tertiary amino group and a vinyl monomer containing a carboxylic acid group. <1> ~ <3> A method for producing a paper sizing agent according to any one of the preceding claims. It is. Effect of the Invention

[0009] By using the paper sizing agent obtained by the method for producing a paper sizing agent of the present invention, paper with excellent sizing performance can be obtained, and in particular the sizing performance of paperboard can be improved. BEST MODE FOR CARRYING OUT THEINVENTION

[0010] The present invention relates to a method for producing a paper sizing agent, characterized in that the paper sizing agent is obtained by using iodine and / or an iodine compound in an amount of 50 ppm or more, calculated as iodine atoms, based on the total amount of monomers used as polymerization components in the following steps (I) and / or (II): (I): A step of polymerizing a copolymer (A) containing a hydrophobic monomer (a1) and a hydrophilic monomer (a2) as polymerization components. (II): A step of polymerizing a hydrophobic monomer (b) in the presence of the copolymer (A) and / or a surfactant.

[0011] According to the method for producing a paper sizing agent of the present invention, it is possible to obtain two types of paper sizing agents, roughly classified as (1) solution type and (2) emulsion type, as follows.

[0012] (1) Solution type The solution-type paper sizing agent is obtained through the above-mentioned process (I). Specifically, the paper sizing agent contains, as a sizing agent component, a copolymer (A) obtained by using a hydrophobic monomer (a1) and a hydrophilic monomer (a2) as polymerization components, polymerizing them in a suitable solvent described below using a radical polymerization initiator, and distilling off the solvent as necessary after the polymerization is completed.

[0013] (2) Emulsion type The emulsion-type paper sizing agent is obtained by the above-mentioned step (II) alone or by the steps (I) and (II). It is a paper sizing agent containing hydrophobic particles as a sizing agent component obtained by emulsion polymerization of a hydrophobic monomer (b) as a polymerization component in the presence of a copolymer (A) and / or a surfactant. In this case, the copolymer (A) may be one obtained by the above-mentioned step (I) or a commercially available one, so long as it is a copolymer containing a hydrophobic monomer (a1) and a hydrophilic monomer (a2) as polymerization components.

[0014] In the method for producing a paper sizing agent of the present invention, iodine and / or iodine compounds are used in an amount of 50 ppm or more in terms of iodine atoms relative to the total amount of monomers used as polymerization components in the steps (I) and / or (II). In other words, iodine and / or iodine compounds may be used in at least one of the steps (I) or (II), and may be used in both steps (I) and (II). However, from the viewpoint of improving sizing properties compared to conventional paper sizing agents that do not use iodine and / or iodine compounds, the amount of iodine and / or iodine compounds must be 50 ppm or more in terms of iodine atoms relative to the total amount of monomers used in each step.

[0015] Examples of iodine and / or iodine compounds include iodine, as well as iodine compounds such as iodoform, potassium iodide, iodoacetic acid, etc. Iodine and / or iodine compounds may be used alone or in combination of two or more.

[0016] The amount of iodine and / or iodine compound used can be appropriately determined depending on the molecular weight of the polymer to be obtained. However, if the amount is too large, the polymer cannot be obtained. Therefore, the amount of iodine and / or iodine compound used is preferably 50 to 50,000 ppm, more preferably 50 to 20,000 ppm, based on the monomer.

[0017] Examples of the hydrophobic monomer (a1) that can be used in step (I) include styrenes such as styrene, α-methylstyrene, vinyltoluene, and divinylbenzene; methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, normal butyl (meth)acrylate, isobutyl (meth)acrylate, tertiary butyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, and the like. Examples of the monomers include alkyl (meth)acrylates such as methacrylate; dialkyl esters of maleic acid and fumaric acid; vinyl esters such as vinyl acetate and vinyl propionate; nitriles such as acrylonitrile and methacrylonitrile; linear α-olefins such as 1-dodecene, 1-tetradecene, 1-hexadecene, and 1-octadecene; cyclic olefins such as cyclohexene; N-alkyl (meth)acrylamides; and alkyl vinyl ethers such as methyl vinyl ether. One of these monomers can be used alone, or two or more can be used in combination. Among these, styrenes and / or alkyl (meth)acrylates are preferred, and more preferred are styrene and / or butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate.

[0018] The hydrophilic monomer (a2) that can be used in the step (I) includes cationic monomers, anionic monomers, and nonionic monomers, and among these, cationic monomers and anionic monomers are preferred. These hydrophilic monomers can be used alone or in combination.

[0019] The cationic monomer may be any vinyl monomer having cationic properties, and specific examples thereof include primary amines such as allylamine, secondary amines such as diallylamine, dialkylaminoalkyl (meth)acrylates such as dimethylaminoethyl (meth)acrylate and dimethylaminopropyl (meth)acrylate, tertiary amines such as (dialkyl)aminoalkyl (meth)acrylamides such as dimethylaminopropyl (meth)acrylamide, and quaternary ammonium salts obtained by quaternizing the above-mentioned cationic monomers with a quaternizing agent, etc. These cationic monomers may be used alone or in combination.

[0020] It is preferable to use a tertiary amine as the cationic monomer, since this is expected to improve the stability and sizing performance of the sizing agent, and among these, dimethylaminoethyl (meth)acrylate and dimethylaminopropyl (meth)acrylamide are more preferable.

[0021] In addition, when the primary to tertiary amines are used, it is preferable to make them into salts using, as a neutralizing agent, a carboxylic acid such as formic acid or acetic acid, an oxycarboxylic acid such as malic acid, tartaric acid or citric acid, or an inorganic acid such as sulfuric acid or hydrochloric acid before or after polymerization in order to impart hydrophilicity.

[0022] Examples of the anionic monomer include a carboxyl group-containing monomer, a sulfonic acid group-containing monomer, a phosphate group-containing monomer, and salts thereof. One or more of these anionic monomers can be used. The anionic monomer is preferably converted into a salt using an alkali such as an alkali metal hydroxide (e.g., sodium hydroxide or potassium hydroxide), an amine base (e.g., ammonia, methylamine, dimethylamine) as a neutralizing agent before or after polymerization, since this can impart hydrophilicity to the anionic monomer.

[0023] Examples of the carboxyl group-containing monomer include acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, their acid anhydrides, neutralized salts, and half esters. Examples of the sulfonic acid group-containing monomer include vinyl sulfonic acid, (meth)allyl sulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, and sulfonated styrene. Examples of the phosphate group-containing monomer include phosphate esters of hydroxyalkyl (meth)acrylates. Among these, it is preferable to use a carboxyl group-containing monomer, and more preferably acrylic acid, methacrylic acid, maleic acid, and their salts. One or more of these anionic monomers can be used.

[0024] Examples of the nonionic monomer include (meth)acrylamide, and hydroxyl group-containing (meth)acrylates such as hydroxyethyl acrylate, hydroxyethyl methacrylate, etc. These nonionic monomers can be used alone or in combination.

[0025] The mass ratio of the hydrophobic monomer (a1) to the hydrophilic monomer (a2) is preferably 50-85:15-50, from the viewpoints of emulsion stability and sizing performance during production, and more preferably 70-85:15-30.

[0026] In addition, a copolymerizable vinyl monomer other than the hydrophobic monomer (a1) and the hydrophilic monomer (a2) may be used as a polymerization component of the copolymer (A) as long as the effect of the paper sizing agent is not impaired. The amount of the copolymerized vinyl monomer is preferably less than 10% by mass of the polymerization components constituting the copolymer (A).

[0027] Examples of the radical polymerization initiator include oil-soluble azo initiators such as 2,2'-azobisisobutyronitrile and dimethyl 2,2'-azobis-(2-methylpropionate); oil-soluble organic peroxides such as benzyl peroxide, tertiary butyl peroxybenzoate and tertiary butyl peroxy-2-ethylhexanoate; persulfates such as ammonium persulfate, potassium persulfate and sodium persulfate; water-soluble peroxides such as hydrogen peroxide; redox polymerization initiators formed by combining these persulfates and peroxides with a reducing agent; water-soluble azo initiators such as 2,2'-azobis(2-amidinopropane)dihydrochloride; and water-soluble organic peroxides such as tertiary butyl hydroperoxide, but are not limited to these, and other known and commonly used polymerization initiators can also be used. Two or more of these polymerization initiators may be used in combination.

[0028] The amount of the polymerization initiator used is usually 0.5 to 10% by mass based on the total amount of the monomers used in the present invention. The polymerization initiator may be charged together with the monomers in a reaction vessel all at once, or may be added dropwise continuously.

[0029] Also, known chain transfer agents can be used, and examples of such agents include α-methylstyrene dimer; alkyl mercaptan compounds such as normal octyl mercaptan, tertiary dodecyl mercaptan, and normal dodecyl mercaptan; mercaptan derivatives such as thioglycolic acid derivatives, mercaptopropionic acid derivatives, mercaptoethanol, thiomalic acid, and thiosalicylic acid; and alcohols such as ethanol and isopropyl alcohol.

[0030] These chain transfer agents may be charged together with the monomers in a reaction vessel at once or may be added dropwise continuously. Two or more of these chain transfer agents may be used in combination. The amount of the chain transfer agent used varies depending on the chain transfer agent used, but is preferably in the range of 0 to 200% by mass based on the total amount of the monomers used in the present invention.

[0031] Examples of the solvent that can be used in the step (I) include water; lower alcohol-based organic solvents such as methyl alcohol, ethyl alcohol, and isopropyl alcohol; aromatic organic solvents such as benzene, toluene, and xylene; ketone-based organic solvents such as acetone and methyl ethyl ketone; and acetic acid-based organic solvents such as acetic anhydride and glacial acetic acid. These organic solvents can be used alone or in combination of two or more. Usually, after polymerization, water and an appropriate amount of a neutralizing agent for the copolymer (A) are mixed to prepare an aqueous solution, but it is preferable that no organic solvent, which is a hazardous material, remains as a paper sizing agent. Therefore, lower alcohol-based solvents and ketone-based organic solvents with a boiling point of less than 100°C that are easy to distill off after polymerization, and toluene that can be distilled off by azeotropy with water are preferably used.

[0032] Examples of the polymerization method in step (I) that can be used include a batch addition polymerization method in which all of the monomers are charged into a reaction vessel at once and polymerized, a divided addition polymerization method in which some or all of the monomers are dividedly added to a reaction vessel and polymerized, and a continuous dropping polymerization method in which some or all of the monomers are continuously dropped into a reaction vessel and polymerized.

[0033] The aqueous solution containing the copolymer (A) obtained in step (I) can be used as a solution-type paper sizing agent as it is, but the aqueous solution can also be used in step (II).

[0034] When a cationic monomer having a tertiary amino group is used as the hydrophilic monomer (a2), it is preferable to quaternize the tertiary amino group of the copolymer by a known and conventional method. Examples of quaternizing agents that can be used for the quaternization include alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide, and oxides such as styrene oxide; organic halides such as methyl chloride, ethyl chloride, benzyl chloride, epichlorohydrin, glycidyl trimethyl ammonium chloride, and 3-chloro-2-hydroxypropyl trimethyl ammonium chloride; dimethyl sulfate, and diethyl sulfate.

[0035] In the step (II), hydrophobic monomer (b) is emulsion-polymerized in water in the presence of copolymer (A) and / or a surfactant to form hydrophobic particles into an emulsion.

[0036] In the present invention, the surfactant refers to a known low molecular weight surfactant, and examples thereof include cationic, nonionic, amphoteric or anionic surfactants and radically polymerizable surfactants, and at least one selected from these groups can be used. The amount of the surfactant used is usually 0 to 10 mass% based on the total amount of the monomers used in the present invention. The surfactant may be charged in a reaction vessel together with the monomers at once, or may be continuously dropped together with the monomers.

[0037] Examples of cationic surfactants include acetates and epichlorohydrin-modified primary and secondary amines, tetraalkylammonium chloride, trialkylbenzylammonium chloride, epichlorohydrin-modified rosinamine acetate, monooxyethylene alkylamines, and polyoxyethylene alkylamines.

[0038] Examples of the anionic surfactant include alkyl sulfates, alkyl ether sulfates, alkylbenzene sulfonates, and alkali salts of naphthalenesulfonate-formaldehyde condensates.

[0039] Examples of the nonionic surfactant include polyoxyalkylene alkyl ethers, polyoxyalkylene alkylphenyl ethers, polyoxyalkylene fatty acid esters, and sorbitan fatty acid esters.

[0040] Further, examples of radically polymerizable surfactants include polyoxyalkylene alkyl ethers, polyoxyalkylene phenyl ethers, and polyoxyalkylene mono- or distyryl phenyl ethers having one or more functional groups having a carbon-carbon double bond in the molecule, such as a (meth)allyl group, a 1-propenyl group, a 2-methyl-1-propenyl group, an isopropenyl group, a vinyl group, and a (meth)acryloyl group, as well as sulfonates and sulfate salts derived therefrom.

[0041] As the hydrophobic monomer (b), any of the monomers listed as the hydrophobic monomer (a1) used in the step (I) can be used, and these monomers can be used alone or in a mixture of two or more. Among these, styrenes and alkyl (meth)acrylates are preferred from the viewpoint of sizing performance and emulsion stability during emulsion polymerization, and styrene and / or butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate are more preferred. Note that a part of the hydrophobic monomer (b) can also be replaced with a vinyl monomer copolymerizable with the hydrophobic monomer (b) within a range that does not impair the effects of the present invention.

[0042] When the copolymer (A) is used in the step (II), the mass ratio of the copolymer (A) to the hydrophobic monomer (b) is preferably (10-100):(0-90) from the viewpoints of the stability and sizing performance of the obtained copolymer, and more preferably (20-100):(0-80).

[0043] In step (II), the hydrophobic monomer (b) is emulsion-polymerized in water using a radical polymerization initiator, and the polymerization method can be any of the conventional polymerization methods that can be used in step (I). In this case, the radical polymerization initiator can be the same as that which can be used in step (I).

[0044] The paper sizing agent obtained by the method for producing a paper sizing agent of the present invention may contain additives such as antioxidants, antifoaming agents, preservatives, chelating agents, water-soluble aluminum compounds, etc., as required.

[0045] The paper sizing agent can be used either as a surface sizing agent or an internal sizing agent for papermaking, but is preferably used as a surface sizing agent.

[0046] Surface sizing agents are applied to base paper to exert a sizing effect mainly on the surface of the paper, while internal sizing agents are added to the pulp slurry before paper is manufactured to exert a sizing effect throughout the paper.

[0047] When used as a papermaking sizing agent, the pulp to be used in the base paper or paper to which it is applied may be bleached or unbleached chemical pulp such as kraft pulp or sulfite pulp, bleached or unbleached high-yield pulp such as groundwood pulp, mechanical pulp or thermomechanical pulp, or waste paper pulp such as recycled newspapers, recycled magazines, recycled cardboard or deinked recycled paper.

[0048] Additives such as water-soluble aluminum compounds such as aluminum sulfate, fillers, dyes, rosin-based sizing agents for acidic papermaking, alkyl ketene dimer-based and alkenyl succinic anhydride-based sizing agents for neutral papermaking, rosin-based sizing agents for neutral papermaking, dry strength agents, wet strength agents, retention aids, drainage aids, coagulants, and defoamers may be added to the slurry obtained by dispersing the pulp in water as necessary to obtain base paper or paper in order to achieve the physical properties required for each paper type. When used as an internal sizing agent, they are added to the pulp slurry. Examples of fillers include clay, talc, titanium oxide, and heavy and light calcium carbonate. These may be used alone or in combination.

[0049] When used as a surface sizing agent, the coating machine that can be used includes a size press, a film press, a gate roll coater, a rod metering coater, a blade coater, a calendar, a bar coater, a knife coater, an air knife coater, a curtain coater, etc. Also, it can be applied to the surface of the base paper by a spray coater.

[0050] When applied as a surface sizing agent, the sizing agent may be used as is or diluted with water, etc., but it may also be used by mixing at least one selected from the group consisting of starches such as oxidized starch, phosphate esterified starch, enzyme-modified starch, ammonium persulfate-modified starch, cationic starch, and amphoteric starch, celluloses such as carboxymethylcellulose, polyvinyl alcohols, polyacrylamides, and water-soluble polymers such as sodium alginate, etc. In addition, additives such as other surface sizing agents, pH adjusters such as aluminum sulfate, conductive agents such as sodium chloride and sodium sulfate, antislip agents, preservatives, rust inhibitors, antifoaming agents, viscosity adjusters, dyes, and pigments may also be used in combination.

[0051] Examples of sized paper that can be obtained using a papermaking sizing agent include various types of paper and paperboard. For example, recording paper such as PPC paper, inkjet recording paper, laser printer paper, form paper, thermal transfer paper, and thermal recording paper; coated paper such as art paper, cast coated paper, and high-quality coated paper; wrapping paper such as kraft paper and pure white roll paper; Western paper such as notebook paper and book paper; newsprint; paperboard for paper containers such as manila cardboard, white cardboard, and chipboard; and paperboard such as liner and medium.

[0052] The concentration of the coating solution when applied as a surface sizing agent is usually 0.1 to 5% by mass, preferably 0.2 to 1% by mass. If it is less than 0.1% by mass, the sizing effect may be insufficient, and if it is used in excess of 5% by mass, the sizing effect is hardly improved further and may be economically disadvantageous, which is not preferred.

[0053] Typically, the coating amount is 0.01 to 1 g / m2 in solid content.2 , preferably 0.02 to 0.2 g / m 2 Within the above range, the sizing effect is particularly excellent. EXAMPLES

[0054] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. In the following, "parts" and "%" mean parts by mass and % by mass, respectively, unless otherwise specified.

[0055] 1-1. Manufacture of paper sizing agents (cationic copolymers) (1) Manufacturing of solution type Example 1 A 1-liter four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen inlet tube was charged with 75 parts of styrene as a hydrophobic monomer (a1), 25 parts of dimethylaminoethyl methacrylate as a hydrophilic monomer (a2), 1.0 parts of iodine as an iodine compound (10,000 ppm as an iodine atom relative to the monomer), 2.0 parts of azobisisobutyronitrile and 50 parts of toluene, and the mixture was kept at 80°C for 7 hours, and then 0.7 parts of azobisisobutyronitrile was added and further kept at the same temperature for 3 hours. Next, 10.6 parts of 90% acetic acid was added as a neutralizing agent, and then 200 parts of water was added to obtain an emulsion, and the temperature was further increased to distill off toluene. Next, 14.7 parts of epichlorohydrin (100 mol % relative to dimethylaminoethyl methacrylate) was added as a quaternizing agent, and the mixture was allowed to react at 60°C for 4 hours. 258 parts of water were then added to obtain a solution-type paper sizing agent containing 20.1% of copolymer (A-1) as a solid content.

[0056] Comparative Example 1 A comparative solution-type paper sizing agent containing copolymer (A-2) was obtained in the same manner as in Example 1, except that iodine and / or an iodine compound was not used.

[0057] Comparative Example 2 To the solution containing the copolymer (A-2) obtained in Comparative Example 1, iodine dissolved in isopropyl alcohol was added in an amount of 10,000 ppm based on the mass of the copolymer before neutralization and quaternization to obtain a solution containing copolymer (A-3), thereby obtaining a solution-type comparative paper sizing agent.

[0058] [Table 1]

[0059] (Explanation of abbreviations in the table) St: styrene DMEM: dimethylaminoethyl methacrylate Epi: epichlorohydrin

[0060] *Added to the solution containing copolymer (A-2) after polymerization.

[0061] (2) Manufacturing of emulsion type Example 2 In a reactor similar to that of Example 1, 500 parts of the aqueous solution of copolymer (A-1) produced in Example 1 (100 parts as solids) was placed, 192 parts of water, 50 parts of isobutyl methacrylate and 50 parts of normal butyl acrylate as hydrophobic monomers (b), 0.10 parts of iodine as an iodine compound (1000 ppm as iodine atoms relative to monomers), and 10 parts by weight of 5% 2,2'-azobis(2-methylpropiondiamidine) dihydrochloride (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.: water-soluble azo polymerization initiator V-50) aqueous solution (hereinafter sometimes simply abbreviated as "5% V-50 aqueous solution") were added, and the temperature was raised to 80 ° C. while mixing and stirring under a nitrogen stream. The emulsion polymerization reaction was completed by holding at 80 ° C. for 4 hours, and an emulsion-type papermaking sizing agent (E-1) with a solids concentration of 25% was obtained.

[0062] (Examples 3 to 16, Comparative Examples 3 to 4) Solutions containing copolymers (A-4) to (A-9) were obtained in the same manner as in Example 1, except that the type and amount of hydrophobic monomer (a1), the type and amount of hydrophilic monomer (a2), the amount of quaternizing agent, and the type and amount of iodine and / or iodine compound were changed as shown in Table 2, and were used in polymerizing the paper sizing agents of Examples 5 to 8, 11, and 12. Next, the type and amount of copolymer (A), the type and amount of hydrophobic monomer (b), and the type and amount of iodine and / or iodine compound were changed as shown in Table 3, and emulsion-type paper sizing agents (E-2) to (E-17) were obtained in the same manner as in Example 2.

[0063] [Table 2]

[0064] (Explanation of abbreviations in the table) St: styrene IBMA: Isobutyl methacrylate TBA: t-butyl acrylate DMEM: Dimethylaminoethyl methacrylate DMPMA: dimethylaminopropyl methacrylamide Epi: epichlorohydrin

[0065] *As iodine atoms

[0066] [Table 3]

[0067] (Explanation of abbreviations in the table) IBMA: Isobutyl methacrylate BA: n-butyl acrylate St: styrene EHA: 2-Ethylhexyl acrylate

[0068] *As iodine atoms

[0069] 1-2. Evaluation test of paper sizing agents as surface sizing agents (Test Example 1) Evaluation of sizing performance on paperboard (1) Paperboard manufacturing 380ml of recycled cardboard pulp with Canadian Standard Freeness, ash content of 10.0%, and pH of 7.0 was used, and aluminum sulfate was added at 1.0% (absolute dry weight basis) based on the pulp, a PAM-based strength agent (Seiko PMC Corporation; DS4433) was added at 0.3% as a strength agent, and a rosin-based sizing agent (Seiko PMC Corporation; CC1401) was added at 0.1% as a sizing agent, in that order, and the slurry was diluted to 0.8% with water having an electrical conductivity of 170mS / m. The diluted pulp slurry was then mixed with a retention aid (Himo Corporation; Himoloc ND300) at 0.01% (absolute dry weight basis) based on the pulp, and the slurry was spun on a Noble and Wood papermaking machine at a basis weight of 120g / m. 2 The pH of the paper was 7.3. The wet paper was dried at 100° C. for 160 seconds using a drum dryer.

[0070] (2) Preparation of coating solution Corn starch (Corn Starch Y, manufactured by Nippon Shokuhin Kako Co., Ltd.) was diluted with water to a concentration of 10%, and 1% ammonium persulfate was added based on the solid content of the starch. The mixture was gelatinized at 95°C for 20 minutes and adjusted to pH 6.0 using sodium hydroxide. The paper sizing agents obtained in Examples 1 to 16 and Comparative Examples 1 to 4 were then added to the mixture to the following solid content concentrations to prepare a coating liquid. Solids concentration of coating liquid: Ammonium persulfate modified starch...6%, paper sizing agent...0.3%

[0071] (3) Paperboard manufacturing and sizing performance evaluation The coating liquid prepared in (2) above was applied to the base paper prepared in (1) above using a size press. The solid coating amount of the surface sizing agent on this coated paper was 0.06 g / m 2After coating, the paper was dried using a drum dryer at 100°C for 80 seconds. The resulting test paper was conditioned for 24 hours in a constant temperature and humidity environment (23°C, 50% relative humidity), and the Cobb water absorbency (120 seconds) (based on JISP8140) was measured. The smaller the Cobb water absorbency value, the better the sizing performance. The evaluation results are shown in Table 4.

[0072] [Table 4]

[0073] The evaluation results show that the papers in Evaluation Examples 1 to 16 in Table 4, which were produced using the papermaking sizing agent of the present invention, have superior sizing performance (Cobb water absorbency) compared to the papers in Comparative Evaluation Examples 1 to 4, which were produced using papermaking sizing agents different from the papermaking sizing agent of the present invention.

[0074] 2-1. Manufacture of paper sizing agents (anionic copolymers) (1) Manufacturing of solution type (Example 17) In a reactor similar to that of Example 1, 70 parts of styrene as a hydrophobic monomer (a1), 30 parts of methacrylic acid as a hydrophilic monomer (a2), 1.2 parts of iodine as an iodine compound (12000 ppm as iodine atoms relative to the monomer), 2.0 parts of azobisisobutyronitrile and 100 parts of isopropyl alcohol were charged, and the mixture was kept at 80 ° C for 7 hours, and then 1.0 part of azobisisobutyronitrile was charged and further kept at the same temperature for 3 hours. Next, 65.2 parts of 30% potassium hydroxide was added as a neutralizing agent, and then 300 parts of water was added, and the temperature was further increased to distill off isopropyl alcohol. Water was added to obtain a solution-type papermaking sizing agent containing 20.2% of copolymer (A-10) as a solid content.

[0075] Comparative Example 5 A comparative solution-type paper sizing agent containing the copolymer (A-11) was obtained in the same manner as in Example 17, except that iodine was not used.

[0076] Comparative Example 6 To the solution containing the copolymer (A-11) obtained in Comparative Example 5, iodine dissolved in isopropyl alcohol was added in an amount of 12,000 ppm based on the mass of the copolymer before neutralization to obtain a solution containing the copolymer (A-12), thereby obtaining a solution-type comparative papermaking sizing agent.

[0077] [Table 5]

[0078] (Explanation of abbreviations in the table) St: styrene MAA: Methacrylic acid KOH: Potassium hydroxide

[0079] *Added to the solution containing copolymer (A-11) after polymerization.

[0080] (2) Manufacturing of emulsion type (Examples 18 to 32, Comparative Examples 7 to 8) Solutions containing copolymers (A-13) to (A-18) were obtained in the same manner as in Example 17, except that the type and amount of hydrophobic monomer (a1), the type and amount of hydrophilic monomer (a2), and the type and amount of iodine and / or iodine compound were changed as shown in Table 6, and were used in polymerizing the sizing agents of Examples 21 to 24, 28, and 29. Next, the type and amount of copolymer (A), the type and amount of hydrophobic monomer (b), and the type and amount of iodine and / or iodine compound were changed as shown in Table 7, and the 5% V-50 aqueous solution was changed to 5% ammonium persulfate, and the same procedure was followed as in Example 2 to obtain emulsion-type paper sizing agents (E-18) to (E-34).

[0081] [Table 6]

[0082] (Explanation of abbreviations in the table) St: styrene IBMA: Isobutyl methacrylate EHA: 2-Ethylhexyl acrylate MAA: Methacrylic acid MAn: Maleic anhydride AA: Acrylic acid IA: Itaconic acid KOH: Potassium hydroxide

[0083] *As iodine atoms

[0084] [Table 7]

[0085] (Explanation of abbreviations in the table) IBMA: Isobutyl methacrylate BA: n-butyl acrylate St: styrene EHA: 2-Ethylhexyl acrylate

[0086] *As iodine atoms

[0087] 2-2. Evaluation test of paper sizing agents as surface sizing agents (Test Example 2) Evaluation of sizing performance on neutral wood-free paper (1) Production of neutral woodfree base paper Pulp (mixed pulp with a 9:1 ratio of hardwood to softwood pulp) beaten to 380 ml Canadian Standard Freeness was prepared into a 2.5% slurry, to which 2% calcium carbonate (TP121S, Okutama Kogyo Co., Ltd.) was added (on an oven-dry weight basis). Next, aluminum sulfate (0.5% by weight of the pulp), cationic starch (Cato304, National Starch Co., Ltd.) (0.5% by weight of the pulp), and alkyl ketene dimer sizing agent (AD1602, Seiko PMC Co., Ltd.) (0.03% by weight of the pulp) were added in that order, and the pulp slurry was then diluted to a concentration of 0.25% with dilution water at pH 7.5. Then, 15% calcium carbonate (TP121S, manufactured by Okutama Kogyo Co., Ltd.) based on the pulp (bone dry weight basis) and 0.01% retention aid (NR12MLS, manufactured by Hymo Co., Ltd.) based on the pulp (bone dry weight basis) were added to the diluted pulp slurry, and the mixture was spun on a Noble and Wood papermaking machine to produce a paper with a basis weight of 65 g / m 2 The pH of the paper was 7.5. The wet paper was dried at 100° C. for 80 seconds using a drum dryer.

[0088] (2) Preparation of coating solution Oxidized starch (MS3800, manufactured by Nihon Shokuhin Kako Co., Ltd.) was diluted with water to a concentration of 10%, and gelatinized at 95°C for 20 minutes. Thereafter, the paper sizing agents obtained in Examples 17 to 32 and Comparative Examples 5 to 8 and sodium chloride (NaCl) were added to obtain the solid content concentrations shown below to prepare a coating liquid. Solids concentration of coating liquid: Oxidized starch...6%, paper sizing agent...0.3%, NaCl...0.5%

[0089] (3) Production of neutral woodfree paper and evaluation of sizing performance The coating liquid prepared in (2) above was applied to the base paper prepared in (1) above using a size press to obtain neutral wood-free paper. The solid content of the paper sizing agent in this coated paper was 0.05 g / m 2After coating, the coating was dried at 100°C for 80 seconds using a drum dryer. The obtained test paper was conditioned for 24 hours in a constant temperature and humidity environment (23°C, 50% relative humidity), and the Stockigt sizing degree was measured in accordance with JIS P8122. A higher Stockigt sizing degree value indicates better sizing performance. The results are shown in Table 8.

[0090] [Table 8]

[0091] The evaluation results show that the papers of Evaluation Examples 17 to 32 in Table 8, which were produced using the papermaking sizing agent of the present invention, have superior sizing performance (Stöckigt sizing degree) compared to the papers of Comparative Evaluation Examples 5 to 8, which were produced using papermaking sizing agents different from the papermaking sizing agent of the present invention.

[0092] 3-1. Manufacturing of paper sizing agents (emulsion type using surfactants) (Example 33) In a reactor similar to that of Example 1, 10 parts (3 parts as solids) of Lipocard T-30 (a surfactant manufactured by Lion Corporation, stearyl trimethyl ammonium chloride) as a surfactant, 292 parts of water, 50 parts of isobutyl methacrylate and 50 parts of normal butyl acrylate as hydrophobic monomers (b), 0.10 parts of iodine as an iodine compound (1000 ppm as iodine atoms relative to monomers) and 10 parts by weight of a 5% V-50 aqueous solution were added, and the mixture was heated to 80°C while being mixed and stirred under a nitrogen stream. The mixture was kept at 80°C for 4 hours to complete the emulsion polymerization reaction, and an emulsion-type papermaking sizing agent (E-35) with a solids concentration of 25% was obtained.

[0093] (Example 34, Comparative Examples 9 and 10) Next, the type of surfactant and the amount of iodine and / or iodine compound used were changed as shown in Table 9, and emulsion-type paper sizing agents (E-36) to (E-38) were obtained in the same manner as in Example 33.

[0094] [Table 9]

[0095] (Explanation of abbreviations in the table) T-30: Lipocard T-30 (surfactant manufactured by Lion Corporation, stearyl trimethyl ammonium chloride) N210: Newcol 210 (surfactant manufactured by Nippon Nyukazai Co., Ltd., alkylbenzene sulfonate) IBMA: Isobutyl methacrylate BA: n-butyl acrylate

[0096] *As iodine atoms

[0097] 3-2. Evaluation test of paper sizing agents as surface sizing agents (Test Example 3) Evaluation of sizing performance on neutral wood-free paper (1) Production of neutral woodfree base paper Pulp (mixed pulp with a 9:1 ratio of hardwood to softwood pulp) beaten to 380 ml Canadian Standard Freeness was prepared into a 2.5% slurry, to which 2% calcium carbonate (TP121S, Okutama Kogyo Co., Ltd.) was added (on an oven-dry weight basis). Next, aluminum sulfate (0.5% by weight of the pulp), cationic starch (Cato304, National Starch Co., Ltd.) (0.8% by weight of the pulp), and alkyl ketene dimer sizing agent (AD1638, Seiko PMC Co., Ltd.) (0.03% by weight of the pulp) were added in that order, and the pulp slurry was then diluted to a concentration of 0.25% with dilution water at pH 7.5. Then, 15% calcium carbonate (TP121S, manufactured by Okutama Kogyo Co., Ltd.) based on the pulp (bone dry weight basis) and 0.1% PAM-based paper strength agent (DS4431, manufactured by Seiko PMC Co., Ltd.) based on the pulp (bone dry weight basis) were added to the diluted pulp slurry, and the mixture was spun on a Noble & Wood paper machine to produce a 65 g / m2 paper. 2 The pH of the paper was 7.5. The wet paper was dried at 100° C. for 80 seconds using a drum dryer.

[0098] (2) Preparation of coating solution Tapioca starch (MKK-100, Matsutani Chemical Industry Co., Ltd.) was diluted with water to a concentration of 10%, and 0.1% of Clistase E5CC (Amano Enzyme Inc.) was added based on the solid content of the starch to form an enzyme-modified starch, which was then gelatinized at 95°C for 20 minutes. The paper sizing agents obtained in Examples 33-34 and Comparative Examples 9-10 were then added to the mixture to the following solid content concentrations to prepare a coating solution. Solids concentration of coating liquid: Enzyme modified starch...7%, paper sizing agent...0.5%

[0099] (3) Production of neutral woodfree paper and evaluation of sizing performance The coating liquid prepared in (2) above was applied to the base paper prepared in (1) above using a size press to obtain neutral wood-free paper. The solid content of the paper sizing agent in this coated paper was 0.08 g / m 2 After coating, the coating was dried using a drum dryer at 100°C for 80 seconds. The obtained test paper was conditioned for 24 hours in a constant temperature and humidity environment (23°C, 50% relative humidity), and the Stockigt sizing degree was measured in accordance with JIS P8122. The results are shown in Table 10.

[0100] [Table 10]

[0101] The evaluation results show that the papers of Evaluation Examples 33 and 34 in Table 10, which were produced using the papermaking sizing agent of the present invention, have superior sizing performance (Stöckigt sizing degree) compared to the papers of Comparative Evaluation Examples 9 and 10, which were produced using papermaking sizing agents different from the papermaking sizing agent of the present invention.

Claims

1. A method for producing a paper sizing agent, characterized in that in the following steps (I) and / or (II), iodine and / or an iodine compound are used in an amount of 50 ppm or more in terms of iodine atoms relative to the total amount of monomers used as polymerization components: (I): A step of polymerizing a copolymer (A) containing a hydrophobic monomer (a1) and a hydrophilic monomer (a2) as polymerization components. (II): A step of polymerizing a hydrophobic monomer (b) in the presence of the copolymer (A) and / or a surfactant.

2. The method for producing a papermaking sizing agent according to claim 1, characterized in that the mass ratio of the hydrophobic monomer (a1) to the hydrophilic monomer (a2) is hydrophobic monomer (a1):hydrophilic monomer (a2)=(50-85):(15-50).

3. 3. The method for producing a papermaking sizing agent according to claim 1, wherein the mass ratio of the copolymer (A) to the hydrophobic monomer (b) is copolymer (A):hydrophobic monomer (b)=(10-100):(0-90).

4. The method for producing a paper sizing agent according to any one of claims 1 to 3, characterized in that the hydrophilic monomer (a2) of the copolymer (A) contains one or more selected from the group consisting of a vinyl monomer containing a tertiary amino group and a vinyl monomer containing a carboxylic acid group.

Citation Information

Patent Citations

  • Sizing agent for paper making

    JP1979006902A

  • Surface sizing agent for papermaking

    JP1996246391A

  • Surface sizing agent for paper manufacturing

    JP1999256496A

  • Surface-sizing agent for paper making

    JP1999279983A

  • Production of styrenic polymer

    JP2000198810A